Building a Community-Based Entrepreneurial Ecosystem for Local Economic Resilience - Bunga Aditi; Olga Theolina Sitorus; Tapi Rondang Ni Bulan; Sopi Pentana; Hafriz Rifki Hafas (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The increasing vulnerability of local economies in the face of global disruptions-ranging from the COVID-19 pandemic to climate change and geopolitical instability-has strengthened the urgency to develop strategies that enhance local economic resilience. This study investigates the role of community-based entrepreneurial ecosystems (CBEE) and social capital (SC) in shaping local economic resilience (LER). A quantitative approach was employed using a cross-sectional survey design with 126 respondents consisting of micro, small, and community-based entrepreneurs. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to assess both measurement and structural models. The findings reveal that CBEE exerts a significant direct effect on LER (β = 0.34; p < 0.001), while SC demonstrates an even stronger impact (β = 0.41; p < 0.001). Moreover, CBEE significantly influences SC (β = 0.56; p < 0.001), and the indirect effect of CBEE on LER through SC is confirmed (β = 0.23; p < 0.001). These results highlight that social capital serves as a critical mediator, translating the institutional and resource support within entrepreneurial ecosystems into tangible local resilience outcomes. The model explains 58% of the variance in LER, suggesting a substantial predictive relevance. Theoretically, this research enriches entrepreneurial ecosystem literature by offering a community-centered perspective that integrates CBEE, SC, and resilience theories. Practically, the study underscores the importance of strengthening community institutions, building trust-based networks, and fostering collaborative mechanisms to ensure inclusive and sustainable local development. In conclusion, developing community-based entrepreneurial ecosystems emerges not only as an economic empowerment strategy but also as a key instrument to achieve inclusive growth and long-term resilience.